Uji Toksisitas Akut Asam Askorbat Per Oral pada Organ Ginjal dan Hepar Tikus (Rattusnorvegicus) Betina Galur Wistar (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effects of acute toxicity of ascorbic acid on the kidney and liver organs of female Wistar rats. The method used in this study is an experimental method with a post-test only control group design model approach. The results showed that the average SGPT level was 61.24 ± 9.416 U / L. While the results of the mean value of blood serum creatinine levels were (1.48) (0.60 - 2.00) Based on bivariate analysis, there was no significant difference in the mean between the treatment and control groups (P